2020
DOI: 10.3389/fphys.2020.00901
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ Metabolism as an Emerging Therapeutic Target for Cardiovascular Diseases Associated With Sudden Cardiac Death

Abstract: In addition to its central role in mediating oxidation reduction in fuel metabolism and bioenergetics, nicotinamide adenine dinucleotide (NAD +) has emerged as a vital co-substrate for a number of proteins involved in diverse cellular processes, including sirtuins, poly(ADP-ribose) polymerases and cyclic ADP-ribose synthetases. The connection with aging and age-associated diseases has led to a new wave of research in the cardiovascular field. Here, we review the basics of NAD + homeostasis, the molecular physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 262 publications
(355 reference statements)
0
19
0
Order By: Relevance
“…However, under HFD feeding, Grx3 CKO DIO mice showed a significant increase in the NAD + /NADH ratio (Figure S1), indicating a redox imbalance in the hearts. There is growing evidence that cardiac energy metabolism and redox balance are crucial for the development and progression of heart diseases including heart failure [17][18][19]. Thus, these results suggest that deletion of Grx3 in the Grx3 CKO DIO hearts leads to oxidative stress and redox imbalance that are detrimental to cardiac function and eventually cause the progression of heart failure in these mice (see below).…”
Section: Enhanced Ros Production In the Heart Of Grx3 Cko Mice Independently Of Feeding Regimementioning
confidence: 95%
“…However, under HFD feeding, Grx3 CKO DIO mice showed a significant increase in the NAD + /NADH ratio (Figure S1), indicating a redox imbalance in the hearts. There is growing evidence that cardiac energy metabolism and redox balance are crucial for the development and progression of heart diseases including heart failure [17][18][19]. Thus, these results suggest that deletion of Grx3 in the Grx3 CKO DIO hearts leads to oxidative stress and redox imbalance that are detrimental to cardiac function and eventually cause the progression of heart failure in these mice (see below).…”
Section: Enhanced Ros Production In the Heart Of Grx3 Cko Mice Independently Of Feeding Regimementioning
confidence: 95%
“…Therefore, NAD + plays a central role in oxidative phosphorylation, making it an attractive target for interventions in cardiac diseases including AF. Indeed, accumulating studies have already shown that boosting NAD + levels improve mitochondrial function in cardiovascular diseases, such as heart failure and ischemic conditions [118][119][120], which has been reviewed in-depth [121]. Collectively, these findings suggest that NAD + homeostasis improves mitochondrial function by attenuation of oxidative stress and DNA damage [118].…”
Section: Nutraceuticals To Conserve Mitochondrial Functionmentioning
confidence: 95%
“…3,4 The decline in NAD + is associated with the development of various CVDs like cardiac hypertrophy and heart failure, while supplementation of NAD + improves cardiac function. 5 Interestingly, the beneficial effects of NAD + supplementation in the heart is mediated by a family of NAD + -dependent enzymes called sirtuins. 6 Sirtuins, the mammalian homologs of the yeast Sir2, are post-translational modification enzymes with diverse histone and nonhistone targets.…”
Section: Introductionmentioning
confidence: 99%